Monte Carlo simulation of Gold and Silver nanoparticles in interaction with strongly surfactant media - Reinaudi, Luis (2013)
The melting and subsequent freezing of Ag and Au nanoclusters consisting of 55 and 147 atoms and interacting with a surfactant medium is studied by Monte Carlo simulations using the embeddedatom method. In our model, the interaction with the surfactant medium is represented by an additional energy term (Q) associated to a surface atom. We observe a decrease in the transition temperature (melting point) with the increase of the value of Q. In some of the systems, before the melting, a solid–solid structural transition takes place as the temperature increases. For large values of the parameter Q, the structures obtained from the freezing tend to have morphologies that have a larger fraction of atoms at the surface and which would be otherwise unstable.